Presenting a Conceptual Model of Financing Mechanisms for Export-Oriented Industries through Domestic and Foreign Resources - Shariatnia, Mona; Jabbarzade, Seyyed Vahid; Kiapour, Azadeh; Masoumi, Shiba (Management Strategies and Engineering Sciences, 2025)
This study aimed to develop a conceptual model of financing mechanisms for export-oriented industries in Iran by integrating domestic and foreign resources through a grounded theory approach. Using a qualitative methodology based on grounded theory, data were collected through in-depth semi-structured interviews with 20 experts, managers, and stakeholders in export-related sectors. The participants were selected using purposive and theoretical sampling methods, and interviews continued until theoretical saturation was achieved. The coding process followed Strauss and Corbin’s three-stage model: open, axial, and selective coding. Data analysis was conducted using thematic categorization and conceptual mapping to structure the emerging model. The Strauss and Corbin paradigmatic framework was employed to organize identified components into six analytical dimensions: causal conditions, contextual conditions, the central phenomenon, intervening conditions, strategies, and consequences. The study identified 23 second-level financing mechanisms such as qard al-hasan contracts, sukuk, equity shares, crowdfunding, and export finance tools. These mechanisms were conceptually organized around the central phenomenon of developing financing mechanisms for export-oriented industries. Causal conditions emphasized the role of Islamic finance and prepayment strategies, while contextual conditions highlighted the influence of supportive policies, financial institutions, and capital markets. Intervening conditions included digital financing and commercial loans, and strategic responses involved equity participation and sukuk feasibility. The outcomes included enhanced capital access, increased investor participation, and the establishment of export clinics. The resulting conceptual model reflects a hybrid financing structure responsive to institutional constraints and global trade dynamics. The findings underscore the need for an integrated, context-sensitive approach to financing export-oriented industries. By aligning traditional Islamic finance with modern instruments and state policies, the proposed model offers a practical and adaptable framework for enhancing export competitiveness and resilience in emerging economies such as Iran.